Temporary Equilibria with Quantity Rationing - Bohm, Volker; Levine, Pierre (Review of Economic Studies, 1979)
Volker Böhm, Pierre Lévine; Temporary Equilibria with Quantity Rationing, The Review of Economic Studies, Volume 46, Issue 2, 1 April 1979, Pages 361–377, https